2009
DOI: 10.1093/chromsci/47.9.762
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Tocopherols in Rice Bran Oil Submitted to Heating at Different Temperatures

Abstract: The objective of this study has been to evaluate the stability of alpha-, (gamma+beta)-, and delta-tocopherols in rice bran oil chemically refined submitted to heating in a heater without air circulation and shielded from light, at temperatures of 100 degrees C and 180 degrees C. The collection of samples took place after 48, 96, 144, 192, 240, 336, and 432 h of heating and were stored in amber-colored flasks and frozen (-18 degrees C). The analyses of tocopherols took place in accordance with the method by Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 27 publications
4
32
0
Order By: Relevance
“…Besides that, Bruscatto et al. () reported that the extent of degradation of tocopherols in rice bran oil was complied with the order of α‐tocopherol > (γ + β) > δ‐tocopherol at 100 and 180 °C, which showed that the α‐tocopherol was the most susceptible to oxidize.…”
Section: Resultsmentioning
confidence: 93%
“…Besides that, Bruscatto et al. () reported that the extent of degradation of tocopherols in rice bran oil was complied with the order of α‐tocopherol > (γ + β) > δ‐tocopherol at 100 and 180 °C, which showed that the α‐tocopherol was the most susceptible to oxidize.…”
Section: Resultsmentioning
confidence: 93%
“…Opposite results were achieved by Calvo et al (2011Calvo et al ( , 2012, who encapsulated walnut and olive oils with the method of freeze-drying and found SFA saturated fatty acids, MUFA monounsaturated fatty acids, PUFA polyunsaturated fatty acids a Increase/decrease compared to the control sample that the content of tocopherols in the encapsulated samples differed insignificantly from that assayed in the samples of control oils. In general, high degradation of tocopherols in all analyzed powders could be explained by the presence of light and oxygen during the drying process (Anwar and Kunz 2011) since these compounds are not resistant to high temperatures (Bruscatto et al 2009). Furthermore, the homogenization process might decrease tocopherols too.…”
Section: Bioactive Compound Content In Encapsulated Pumpkin Seed Oilmentioning
confidence: 99%
“…The tocols content (both tocotrienols and tocopherols) of RBD samples were evaluated by reversed-phase HPLC which is equipped with LC-10AV VP pumps, SPD-10AV VP (Shimadzu, Japan) and fluorescent detector (Bruscatto et al, 2009). The KINETEX PFP column (150 mm × 4.6 mm; 100 A), was used (Phenomenex, USA) and 90% methanol in deionized water acts as mobile phase.…”
Section: Determination Of Tocols Contentmentioning
confidence: 99%